The Meaning Of Resorative Justice In The Concepts Of Sulh, Afw, Diyat, And Social Reintegration In Islamic Criminal Law - Abdul Hakim; M. Arief Fadhilah (AT-TAFAHUM: Journal of Law, 2021)
This study aims to explore and analyze the meaning of restorative justice within the framework of Islamic criminal law through the concepts of sulh, afw, diyat, and social reintegration. The research method used is library research with a normative-descriptive approach that examines secondary data in the form of legal and sharia literature. The results show that Islamic criminal law has fundamental similarities with the principles of modern restorative justice, where case resolution does not only focus on punishment (retributive), but rather prioritizes restoring relationships between the perpetrator, victim, and society. The concepts of sulh (peace) and afw (forgiveness) provide space for reconciliation, while diyat (compensation) functions as an instrument for restoring the victim's material rights. Through the islah mechanism, Islamic law encourages social reintegration that allows perpetrators to improve themselves and maintain social harmony. This harmonization between positive law in Indonesia and the values of Islamic criminal law has the potential to become a new paradigm in a more humane and just criminal justice system.